Medvrstniško nasilje in učno delovanje (Celostni pristop k medvrstniškemu nasilju: Psihosocialni konteksti in raziskovalne strategije, 2025)
Peer violence can have a number of consequences, including reduced levels of academic engagement and academic performance. Although the negative association between involvement in peer violence and academic performance is well documented, the mechanisms of this association are not yet fully understood. In this chapter, we summarize the current knowledge on the association between these variables, with an emphasis on contemporary models that, in the context of peer violence, explain the importance of the interaction of student characteristics with the characteristics of their environment. We also present preliminary results of the analysis of the association between different aspects of involvement in peer violence, academic engagement and academic performance in Slovenian eighth and ninth grade students across three time points of measurement. Our findings confirm previous research and represent an important starting point for further study of more complex moderation and mediation models that contribute to the development of appropriate programs to address peer violence.